KEWENANGAN WAKIF TERHADAP HARTA BENDA WAQAF - Usanti, Trisadini Prasastinah; Aryatie, Indira Retno; Yuniarti (Lex Journal: Kajian Hukum & Keadilan, 2021)
Waqf assets are wakif property which can be proven by proof of ownership of the said assets. The types of waqf assets include immovable and movable objects. The formulation of the problem to be analyzed is the wakif authority over waqf assets. The approach used is a statute approach and a conceptual approach. With regard to immovable objects, the proof of ownership of the said property is a certificate of land rights, if the waqf property is in the form of land rights, then the authority to act as wakif is the name printed on the certificate. The meaning of movable objects in the Waqf Law can be categorized into registered objects and unregistered objects. For a registered movable object, there is proof of ownership, so the authority is the name written in the proof of ownership, while the unregistered movable object applies the principle in Article 1977 BW that whoever controls the object is deemed the owner of the object, then the competent authority is the one who controls the object in good faith.